ANALISIS PENERAPAN “MATERIAL REQUIREMENT PLANNING (MRP)” DALAM PENGENDALIAN PERSEDIAAN BAHAN BAKU PANEL PADA PT. CAHAYA BUANA INTITAMA DI BOGOR - Rizki Ahmad Fauzi (Jurnal Ilmiah Binaniaga, 2011)
One strategy is to increase productivity by enhancing the company's inventory management system to support the smooth day-to-day operations, the company hopes to establish the amount of raw material inventories efficiently, besides it can reduce the undesirable things, such as: Stock material less raw, raw material stock of redundant, inefficient, disorganized inventory layout, handling errors resulting in damage to the raw materials and others. Models control conducted by PT. Cahaya Buana Intitama is currently using two techniques, namely the calculation of average calculation and the calculation of the last three months the average per period (total months of the current year) to obtain the "Purchase Plan".Keywords: productivity, raw materials, control, material requirements planning.